Single inhaler with beclometasone, formoterol, and glycopyrronium versus triple therapies in adults with uncontrolled asthma: a systematic review and meta-analysis - Fulvio Braido; Ioanna Vlachaki; Georgios F. Nikolaidis; Dimitrios Tzelis; Ifigeneia Barouma; Alessio Piraino; Alessandra Madoni; Nicola Scichilone (Scientific Reports)
Abstract Recent literature has shown that triple therapy is more effective than dual therapy for individuals with uncontrolled asthma. However, the comparative efficacy between different triple therapies remains unclear. The objective of this study was to determine the comparative efficacy of extra-fine single-inhaler medium-dose (MD) or high-dose (HD) of beclometasone/formoterol/glycopyrronium bromide (BDP/FOR/GLY) compared to other triple therapies in patients whose asthma remains uncontrolled with MD or HD inhaled corticosteroids and long-acting β2-agonists. A systematic literature review identified randomized control trials on adult patients with uncontrolled asthma. Two separate networks were constructed according to patients’ previous inhaled-corticosteroid dosage. Network meta-analyses evaluated severe and moderate-to-severe exacerbations, pre-dose forced expiratory volume, and asthma control questionnaire responses at 52 (± 3) weeks. Among single-inhaler triple therapies, MD BDP/FOR/GLY significantly reduced the risk of severe exacerbations (RR [95% CrI] compared to MD fluticasone/umeclidinium/vilanterol: 0.65 [0.49, 0.89]), while HD BDP/FOR/GLY demonstrated an improved trend in reducing severe and moderate-to-severe exacerbations versus HD indacaterol acetate/glycopyrronium bromide/mometasone, fluticasone/umeclidinium/vilanterol, and salmeterol/fluticasone + tiotropium. HD BDP/FOR/GLY and HD BDP/FOR + tiotropium did not differ significantly. Compared to relevant single-inhaler triple therapies, MD and HD BDP/FOR/GLY are associated with a significant benefit or trend for improvement in terms of reducing the rate of severe and moderate-to-severe exacerbations.